BMPs Enhance in Vitro Tissue Regeneration by Human Degenerated Nucleus Pulposus Cells. (May 2014) - Krouwels, A.; Iljas, L.; Plomp, S.; Dhert, W.; Oner, C.; Creemers, L.
Introduction: Bone morphogenetic proteins (BMPs) are currently being investigated for differentiation of stem cells or enhancement of tissue production for various cell types. It has been shown that heterodimers of BMPs can be more effective than the combined homodimers. 1 In this study, we investigate whether this is also true for tissue regeneration by human degenerated NP cells. Materials and Methods: Nucleus pulposus (NP) cells from a human donor (Thompson grade III) were cultured for 14 days in high density (1 × 10^6 cells/cm 2 ) on collagen II coated filters. Several rhBMPs (BMP2, BMP4, BMP7, BMP2+7, BMP4+7 and the heterodimers of BMP2, 7 and BMP4, 7) were added to the culture medium (DMEM + 10% heat inactivated fetal bovine serum + 2% ascorbic acid-2-phosphate) in two different concentrations (total concentration 10 or 100 ng/mL medium). Control medium contained 10 ng/mL TGF-β2. Samples were stained with Safranin O for glycosaminoglycans (GAGs) and with immunohistochemistry for collagen II. Matrix content as reflected by GAG production was measured with a dimethylmethylene blue (DMMB) assay and DNA content with a PicoGreen assay. Statistical analyses included one-way ANOVA and post hoc Bonferroni. Results: GAG per DNA was highest for BMP4 (see Fig. 1 for p values). At 10 ng/mL, the heterodimer of BMP2, 7 resulted in more GAG/DNA than the homodimers combined ( p = 0.003) or BMP7 alone ( p = 0.003), but not for 100 ng/mL. GAG per DNA was higher at 100 ng/mL BMP versus 10 ng/mL for all BMPs ( p < 0.001). Conclusion: In conclusion, BMP4 seems to be the most potent factor for improving matrix production by NP cells in vitro. The heterodimers of BMP2, 7 and BMP4, 7 do not seem to be clearly more effective for tissue production than the homodimers combined or alone, especially for higher concentrations. Disclosure of Interest None declared Reference Israel DI, Nove J, Kerns KM, et al. Heterodimeric bone morphogenetic proteins show enhanced activity in vitro and in vivo. Growth Factors 1996;13(3-4):291–300